Stereoelectronic Properties of 1,2,4-Triazole-Derived N-heterocyclic Carbenes - A Theoretical Study - Ha, Nguyen Van; Dat, Doan Thanh; Nguyet, Trieu Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4, 2019)
A theoretical study on stereo and electronic properties of a series of six 1,2,4-triazole-derived carbenes bearing different N4-substituents, namely isopropyl ( 1 ), benzyl ( 2 ), phenyl ( 3 ), mesityl ( 4 ), 2,6-diisopropylphenyl ( 5 ) and 1-naphthyl ( 6 ), has been carried out. Structures of the six carbenes were first optimized using Gaussian® 16 at B3LYP level. Their molecular geometries and electronic structures of the frontier orbitals were examined. The results suggest the similarity in nature of their HOMOs, which all posses s symmetry with respect to the heterocycle and essentially be the lone electron pair on the C carbene . Steric properties of the NHCs was also quantified using percent volume burried (% V bur ) approach. The NHC 1 with isopropyl N4-substituent was the least bulky one with % V bur of 27.7 and the most sterically demanding carbene is 6 , which has large 2,6-diisopropylphenyl substituent (% V bur = 38.4). Interestingly, the NHCs with phenyl and 1-naphthyl N4-substituents display flexible steric hindrance due to possible rotation of the phenyl or 1-naphthyl around the N-C single bond. Beside stereoelectronic properties of the NHC, topographic steric map of their complexes with metal were also investigated. Keywords : N-heterocyclic carbene, triazolin-5-ylidene, stereoelectronic properties, percent volume burried. References [1] D. Bourissou, O. Guerret, F.P. Gabbaï, G. Bertrand, Stable Carbene, Chem. Rev. 100 (2000) 39−92. https://doi.org/10.1021/cr940472u. [2] N. Marion, S.P. Nolan, Well-Defined N-Heterocyclic Carbenes-Palladium(II) Precatalysts for Cross-Coupling Reactions, Acc. Chem. Res. 41 (2008) 1440−1449. https://doi.org/10.1021/ ar800020y. [3] F.E. Hahn, M.C. Jahnke, Heterocyclic carbenes: synthesis and coordination chemistry, Angew. Chem., Int. Ed. 47 (2008) 3122−3172. http://doi. org/10.1002/anie.200703883. [4] M.N. Hopkinson, C. Richter, M. Schedler, F. Glorius, An overview of N-heterocyclic carbenes, Nature 510 (2014) 485−496. https://doi.org/ nature13384. [5] W.A. Herrmann, N‐Heterocyclic Carbenes: A New Concept in Organometallic Catalysis, Angew. Chem., Int. Ed. 41 (2002) 1290−1309, https://doi.org/10.1002/1521-3773%2820020415 %2941%3A8%3C1290%3A%3AAID-ANIE12 90%3E3.0.CO%3B2-Y. [6] S. Díez-Gonzalez, N. Marion, S.P. Nolan, N-Heterocyclic Carbenes in Late Transition Metal Catalysis, Chem. Rev. 109 (2009) 3612−3676. https://doi.org/10.1021/cr900074m. [7] L. Cavallo, A. Correa, C. Costabile, H.J. Jacobsen, Steric and electronic effects in the bonding of N-heterocyclic ligands to transition metals, Organomet. Chem. 690 (2005) 5407 -5413. https://doi.org/10.1016/j.jorganchem.2005. 07.012. [8] H. Clavier, S.P. Nolan, Percent buried volume for phosphine and N-heterocyclic carbeneligands: steric properties in organometallic chemistry, Chem. Commun. 46 (2010) 841−861. https://doi. org/10.1039/B922984A. [9] C. Buron, L. Stelzig, O. Guerret, H. Gornitzka, V. Romanenko, G. Bertrand, Synthesis and structure of 1,2,4-triazol-2-ium-5-ylidene complexes of Hg(II), Pd(II), Ni(II), Ni(0), Rh(I) and Ir(I), J. Organomet. Chem. 664 (2002) 70-76. https: //doi.org/10.1016/S0022-328X(02)01924-1. [10] S. Guo, H.V. Huynh, Dinuclear Triazole-Derived Janus-Type N-Heterocyclic Carbene Complexes of Palladium: Syntheses, Isomerizations, and Catalytic Studies toward Direct C5-Arylation of Imidazoles, Organometallics, 33 (2014) 2004−2011. https:// doi.org/10.1021/om500139b. [11] A. Zanardi, J.A. Mata, E. Peris, Palladium Complexes with Triazolyldiylidene. Structural Features and Catalytic Applications, Organometallics 28 (2009) 4335−4339. https:// doi.org/10.1021/om8010504. [12] C. Dash, M.M. Shaikh, R.J. Butcher, P. Ghosh, A comparison between nickel and palladium precatalysts of 1,2,4-triazole based N-heterocyclic carbenes in hydroamination of activated olefins, Dalton Trans. 39 (2010) 2515-2524. http://doi.org/10.1039/B917892A. [13] H. Clavier, A. Correa, L. Cavallo, E.C. Escudero-Adan, J. Benet-Buchholz, A.M.J. Slawin, S.P. Nolan, [Pd(NHC) (allyl)Cl] Complexes: Synthesis and Determination of the NHC Percent Buried Volume (%Vbur) Steric Parameter, Eur. J. Inorg. Chem. 2009 (2009) 1767−1773. https:// doi.org/10.1002/ejic.200801235. [14] D. Yuan, H.V. Huynh, Hetero-dicarbene Complexes of Palladium(II): Syntheses and Catalytic Activities, Organometallics, 33 (2014) 6033−6043. https://doi.org/10.1021/om500659v. [15] V.H. Nguyen, I.B. Ibrahim, H.V. Huynh, Postmodification Approach to Charge-Tagged 1,2,4-Triazole-Derived NHC Palladium(II) Complexes and Their Applications Organometallics, 36 (2017) 2345–2353. https:// doi.org/10.1021/acs.organomet.7b00329. [16] V.H. Nguyen, B.M.E. Ali, H.V. Huynh, Stereoelectronic Flexibility of Ammonium-Functionalized Triazole-Derived Carbenes: Palladation and Catalytic Activities in Water Organometallics, 37 (2018) 2358–2367. https:/ /doi.org/10.1021/acs.organomet.8b00347. [17] A.D. Becke, Density‐functional thermochemistry. III. The role of exact exchange, J. Chem. Phys. 98 (1993) 5648-5652. https://doi.org/10.1063/ 1.464913. [18] C. Lee, W. Yang, R.G. Parr, Development of the Colle-Salvetti correlation-energy formula into a functional of the electron density, Phys. Rev. B, 37 (1988) 785-789. https://doi.org/10.1103/ Phys RevB.37.785. [19] S.H. Vosko, L. Wilk, M. Nusair, Accurate spin-dependent electron liquid correlation energies for local spin density calculations: a critical analysis, Can. J. Phys. 58 (1980) 1200-1211. https://doi. org/10.1139/p80-159. [20] P.J. Stephens, F.J. Devlin, C.F. Chabalowski, M.J. Frisch, Ab Initio Calculation of Vibrational Absorption and Circular Dichroism Spectra Using Density Functional Force Fields, J. Phys. Chem. 98 (1994) 11623-11627. https://doi.org/ 10.1021/j100096a001. [21] G.A. Petersson, A. Bennett, T.G. Tensfeldt, M.A. Al-Laham, W.A. Shirley, J. Mantzaris, A complete basis set model chemistry. I. The total energies of closed‐shell atoms and hydrides of the first‐row elements, J. Chem. Phys. 89 (1988) 2193− 2218. https://doi.org/10.10631.455064. [22] G.A Petersson, M.A. Al-Laham, A complete basis set model chemistry. II. Open‐shell systems and the total energies of the first‐row atoms, J. Chem. Phys. 94 (1991) 6081−6090. https://doi. org/10.1063/1.460447. [23] L. Falivene, R. Credendino, A. Poater, A. Petta, L. Serra, R. Oliva, V. Scarano, L. Cavallo, SambVca 2. A Web Tool for Analyzing Catalytic Pockets with Topographic Steric Maps, Organometallics, 35 (2016) 2286–2293. https://doi.org/ 10.1021/acs.organomet.6b00371. [24] D. Enders, K. Breuer, G. Raabe, J. Runsink, J.H. Teles, J. Melder, K. Ebel, S. Brode, Preparation, Structure, and Reactivity of 1,3,4‐Triphenyl‐4,5‐dihydro‐1H‐1,2,4‐triazol‐5‐ylidene, a New Stable Carbene, Angew. Chem. Int. Ed. Engl. 34 (1995) 1021-1023. https://doi.org/10.1002/anie. 199510211. [25] C.A. Tolman, Phosphorus ligand exchange equilibriums on zerovalent nickel. Dominant role for steric effects, J. Am. Chem. Soc. 92 (1970) 2956-2965. https://doi.org/10.1021/ja00713a007. [26] C.A. Tolman, Steric effects of phosphorus ligands in organometallic chemistry and homogeneous catalysis, Chem. Rev. 77 (1977) 313–348. https://doi.org/10.1021/cr60307a002. [27] A. Immirzi, A. Musco, A method to measure the size of phosphorus ligands in coordination complexes, Inorg. Chim. Acta 25 (1977) L41–L42. https://doi.org/10.1016/S0020-1693(00)95 635-4. [28] B.J. Dunne, R.B. Morris, A.G. Orpen, Structural systematics. Part 3. Geometry deformations in triphenylphosphine fragments: a test of bonding theories in phosphine complexes, J. Chem. Soc., Dalton Trans. (1991) 653–661. https://doi.org/ 10.1039/DT9910000653. [29] T.L. Brown, A molecular mechanics model of ligand effects. 3. A new measure of ligand steric effects, Inorg. Chem. 31 (1992) 1286–1294. https://doi.org/10.1021/ic00033a029. [30] H. Clavier, S.P. Nolan, Percent buried volume for phosphine and N-heterocyclic carbeneligands: steric properties in organometallic chemistry Chem. Comm. (2010) 841–861. http://doi.org/ 10.1039/B922984A.